Evaluation Of The Surface Integrity When Machining LM6 Aluminum Metal Matrix Composites Using Coated And Uncoated Carbide Cutting Tools - Abu Bakar, Mohd Hadzley; Ahmad, Siti Sarah Nadia; Raja Abdullah, Raja Izamshah; Md Ali, Mohd Amran; Kasim, Mohd Shahir; Sulaiman, Mohd Amri; Mohamad Raffi, Nurul Fatin (Trans Tech Publications, 2014)
-